Host genetic diversity limits parasite success beyond agricultural systems: a meta-analysis - Ekroth, AKE; Rafaluk-Mohr, C; King, KC (Royal Society, The, 2019)
There is evidence that human activities are reducing the population genetic diversity of species worldwide. Given the prediction that parasites better exploit genetically homogeneous host populations, many species could be vulnerable to disease outbreaks. While agricultural studies have shown the devastating effects of infectious disease in crop monocultures, the widespread nature of this diversity–disease relationship remains unclear in natural systems. Here, we provide broad support that high population genetic diversity can protect against infectious disease by conducting a meta-analysis of 23 studies, with a total of 67 effect sizes. We found that parasite functional group (micro- or macroparasite) affects the presence of the effect and study setting (field or laboratory-based environment) influences the magnitude. Our study also suggests that host genetic diversity is overall a robust defence against infection regardless of host reproduction, parasite host range, parasite diversity, virulence and the method by which parasite success was recorded. Combined, these results highlight the importance of monitoring declines of host population genetic diversity as shifts in parasite distributions could have devastating effects on at-risk populations in nature.